(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
As it is known all publishing scientific information and internet materials in all over the word are not translated into Uzbek, majority parts are expressed in English language. Therefore, the main aim of teaching foreign languages in all institutions in the Republic of Uzbekistan and at the faculties whose major is not a foreign language is teaching so that they can get information which they need by reading texts in English concerning their profession and can communicate orally in English according to their specialty.